2004
DOI: 10.1023/b:emas.0000038187.33602.c0
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Considerations for Establishment of Baseline Loadings from Forested Watersheds for TMDL Application

Abstract: Abstract. Five methods for estimating maximum daily and annual nitrate (NO?) and suspended sediment loads using periodic sampling of varying intensities were compared to actual loads calculated from intensive stormflow and baseflow sampling from small, forested watersheds in north central West Virginia to determine if the less intensive sampling methods were accurate and could be utilized in TMDL development. There were no siflificant differences between the annual NO3 load estimates using non-intensive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…[14] Concentration-discharge (C-Q) relationships have long been used to calculate sediment and chemical loads in streams and rivers [Johnson et al, 1969;Dann et al, 1986;Murdoch, 1991;Murdoch et al, 1998;Edwards et al, 2003]. Inherent in this method is the assumption that the relationship between flow and concentration is consistent over the period of interest (decade, year, season, etc), so that selected samples that span the range of flows observed during that period can be used to estimate concentrations at all flows when samples were not collected.…”
Section: Methods Of Trend Analysismentioning
confidence: 99%
“…[14] Concentration-discharge (C-Q) relationships have long been used to calculate sediment and chemical loads in streams and rivers [Johnson et al, 1969;Dann et al, 1986;Murdoch, 1991;Murdoch et al, 1998;Edwards et al, 2003]. Inherent in this method is the assumption that the relationship between flow and concentration is consistent over the period of interest (decade, year, season, etc), so that selected samples that span the range of flows observed during that period can be used to estimate concentrations at all flows when samples were not collected.…”
Section: Methods Of Trend Analysismentioning
confidence: 99%
“…The significant and positive correlations suggest that it would be less likely for the flush of NO 3 ‐N to appear where a large amount of NO 3 ‐N was available in the forested watersheds of the so‐called N‐saturation regions such as Nagano and Tokyo. Edwards et al (2004) also observed less variability in the concentration of NO 3 ‐N in the N‐saturated watersheds than those in non‐saturated watersheds. For most of the recorded events in Nagano and Tokyo, there was enough NO 3 ‐N available to allow higher NO 3 ‐N concentrations to occur throughout the rainfall events unlike the dilution at Mie and Kochi (Shindo, 2004).…”
Section: Resultsmentioning
confidence: 93%
“…Such non‐point‐source pollution in forested watersheds resulting from stormwater runoff has been identified as one of the major causes of the deterioration of waters downstream. Many researchers have inferred that storm events contribute significantly to the annual load as a result of increased chemical concentrations and increased runoff volume (Ahearn et al , 2004; Edwards et al , 2004; Inamdar et al , 2006; McBroom et al , 2006). The mechanism controlling hydrochemical response to storm event or hydrograph has been well documented for a variety of forested catchments throughout the world by the hydrological and biogeochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the 47 watersheds exhibited little change in rank, which indicates that a two-time survey can serve as an adequate index to stream nitrate concentrations. Also, Edwards et al (2004) showed that relatively low intensity stream sampling (quarterly) in WV could be used to predict actual stream nitrate loads from forested watersheds as accurately as more intensive sampling (weekly) because of the small fluctuation in nitrate concentrations over flow and time.…”
Section: Resultsmentioning
confidence: 99%